American Government and Politics Today: The Essentials, 19th Edition - Barbara A. Bardes; Mack C. Shelley; Steffen W. Schmidt (Cengage Learning, 2019)
Making politics personal, Bardes/Shelley/Schmidt's American Government and Politics Today, The Essentials, Enhanced 19th Edition equips you with the tools and insight to become an active, informed citizen. Unbiased, updated with Election 2018 analysis and extremely student-friendly, the text combines a conversational, easy-to-read style with thorough coverage in a streamlined format. Political authorities as well as longtime professors who know what today's students like, the authors incorporate a wealth of current, compelling and thought-provoking examples that bring chapter concepts to life. In addition, numerous hands-on activities help you figure out where you stand on key issues so you can put your views into action. Also available: MindTap, Cengage Learning's fully online learning solution.